Job embeddedness, work engagement and turnover intention of staff in a higher education institution: An exploratory study - Ndayiziveyi Takawira; Melinde Coetzee; Dries Schreuder (SA Journal of Human Resource Management, 2014)
Orientation: The world economy is becoming increasingly knowledge driven, and intellectual capital is now considered as a human resource that affords organisations a competitive advantage. A high turnover rate in higher education and the importance of retaining staff are concerns that have resulted in increased interest in psychological variables, such as job embeddedness and work engagement that may influence employee retention. Research purpose: The objective of this study was to explore the relationship between job embeddedness, work engagement and turnover intention of staff in a higher education institution. Motivation for the study: Research on how employees’ job embeddedness and work engagement influence their turnover intention is important in the light of organisational concerns about retaining knowledgeable staff in the current higher education environment. Research design, approach and method: A cross-sectional quantitative survey was conducted on a non-probability purposive sample (N = 153) of academic and non-academic staff in a South African higher education institution.